2009
DOI: 10.1007/s00248-009-9604-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Earthworms Lumbricus terrestris and Aporrectodea caliginosa on Bacterial Diversity in Soil

Abstract: Earthworms ingest large amounts of soil and have the potential to radically alter the biomass, activity, and structure of the soil microbial community. In this study, the diversity of eight bacterial groups from fresh soil, gut, and casts of the earthworms Lumbricus terrestris and Aporrectodea caliginosa were studied by single-strand conformation polymorphism (SSCP) analysis using both newly designed 16S rRNA gene-specific primer sets targeting Alphaproteobacteria, Betaproteobacteria, Gammaproteobacteria, Delt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
43
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(51 citation statements)
references
References 52 publications
8
43
0
Order By: Relevance
“…(most abundant in both clone libraries), and some other proteobacteria, (ii) bacterivorous protists, (iii) bacteria capable of symbiosis with protists, e.g., Legionellarelated organisms, and (iv) quite surprisingly, highly diverse verrucomicrobia, planctomycetes, stramenopiles, and other microbes probably consuming products from fermentative processes. Previously we observed that cellvibrios were rather diverse in the soil substratum and enigmatic in the casts (54). Their abundance in cultures could indicate an ability to transiently flourish and quickly colonize cellulosic substrates upon their release with the cast.…”
Section: Discussionmentioning
confidence: 99%
“…(most abundant in both clone libraries), and some other proteobacteria, (ii) bacterivorous protists, (iii) bacteria capable of symbiosis with protists, e.g., Legionellarelated organisms, and (iv) quite surprisingly, highly diverse verrucomicrobia, planctomycetes, stramenopiles, and other microbes probably consuming products from fermentative processes. Previously we observed that cellvibrios were rather diverse in the soil substratum and enigmatic in the casts (54). Their abundance in cultures could indicate an ability to transiently flourish and quickly colonize cellulosic substrates upon their release with the cast.…”
Section: Discussionmentioning
confidence: 99%
“…Mycobacteriumrelated narG sequences have been retrieved from soil (14,49), species of Mycobacterium can reduce nitrate to nitrite (73), and mycobacterial species and other Actinobacteria occur in earthworm guts and casts and might be associated with gut walls (9,23,24,37,69). Furthermore, the percentages of Actinobacteriarelated 16S rRNA genes can be higher in earthworm gut and cast than in soil (24,47) (41), but the nitrate reductase encoded by this operon might also dissimilate nitrate (63,73). The detection of Mycobacterium-related narG transcripts in the earthworm gut and wet, uppermost soil suggests that the encoded nitrate reductase is important for the dissimilation and/or assimilation of nitrate.…”
Section: Discussionmentioning
confidence: 99%
“…However, the propensity of earthworms to consume and transform their habitat has significant impact on terrestrial ecosystems and soil processes (Darwin, 1881;Lee, 1985;Edwards and Bohlen, 1996;Makeschin, 1997;Brown and James, 2006;Nechitaylo et al, 2010). For example, Lumbricus terrestris can consume the entire annual litter fall (300 g m À 2 ) of forests it inhabits (Satchell, 1967).…”
Section: Introductionmentioning
confidence: 99%